2017
DOI: 10.1111/mpp.12551
|View full text |Cite
|
Sign up to set email alerts
|

FcRav2, a gene with a ROGDI domain involved in Fusarium head blight and crown rot on durum wheat caused by Fusarium culmorum

Abstract: Fusarium culmorum is a soil-borne fungal pathogen which causes foot and root rot and Fusarium head blight on small-grain cereals, in particular wheat and barley. It causes significant yield and quality losses and results in the contamination of kernels with type B trichothecene mycotoxins. Our knowledge of the pathogenicity factors of this fungus is still limited. A transposon tagging approach based on the mimp1/impala double-component system has allowed us to select a mutant altered in multiple metabolic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…Compounds 1-15 belong to cinnamic acids (1-3 and 15), gallic esters (4 and 5), monoterpenoids (6-9), phenylpropanoids (11)(12)(13)(14) and phenylethanones (10). Except for 8 and 9, all compounds share a common phenol ring with a functional group in the para position (i.e., compounds 1-5 and 10-15) or in the ortho position (i.e., compounds 6 and 7) to the hydroxyl group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds 1-15 belong to cinnamic acids (1-3 and 15), gallic esters (4 and 5), monoterpenoids (6-9), phenylpropanoids (11)(12)(13)(14) and phenylethanones (10). Except for 8 and 9, all compounds share a common phenol ring with a functional group in the para position (i.e., compounds 1-5 and 10-15) or in the ortho position (i.e., compounds 6 and 7) to the hydroxyl group.…”
Section: Discussionmentioning
confidence: 99%
“…A set of naturally occurring compounds belonging to cinnamic acids (compounds 1-3 and 15), gallic esters (4 and 5), terpenes (6-9), phenylpropanoids (11)(12)(13)(14) and one phenylethanone (10) were selected (Figure 1). Moreover, compound NPD352 (testosterone 3-(O-carboxymethyl)oxime amide-bonded to phenylalanine methyl ester), a trichodiene inhibitor identified by chemical array and library screening using a recombinant TRI5 expressed in Escherichia coli [52], was included in the docking analysis.…”
Section: Docking Of Phenols and Hydroxylated Biphenyls To Tri5mentioning
confidence: 99%
See 1 more Smart Citation
“…It also confirms functional analyses of genes from wheat-infecting Fusarium species. Different genes were reported to be equally involved in the pathogenic mechanisms of both FHB and FFR (Spanu et al, 2012, 2018; Pasquali et al, 2013). From a physiopathological point of view, F. graminearum shows a common infection process during both root- and head infection (Wang Q. et al, 2015; Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a hypothetical protein (FcRav2) with ROGDI such as leucine zipper domain, and homologous to yeast Rav2 was reported in F. culmorum . It was demonstrated that FcRav2 protein may become a suitable target for new antifungal drug development or the plant–mediated resistance response in filamentous fungi of agricultural interest ( Spanu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%